2017
DOI: 10.1063/1.5006694
|View full text |Cite
|
Sign up to set email alerts
|

Percolating transport in superconducting nanoparticle films

Abstract: Nanostructured and disordered superconductors exhibit many exotic fundamental phenomena, and also have many possible applications. We show here that films of superconducting lead nanoparticles with a wide range of particle coverages, exhibit non-linear V(I) characteristics that are consistent with percolation theory. Specifically, it is found that V / ðI À I c Þ a , where a ¼ 2.1 6 0.2, independent of both temperature and particle coverage, and that the measured critical currents (I c) are also consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…At lower currents, pulsed current measurements are consistent with the BKT and breakdown behaviour observed using DC currents. Detailed discussion of these measurements will be presented elsewhere [58].…”
Section: Critical Currentsmentioning
confidence: 99%
“…At lower currents, pulsed current measurements are consistent with the BKT and breakdown behaviour observed using DC currents. Detailed discussion of these measurements will be presented elsewhere [58].…”
Section: Critical Currentsmentioning
confidence: 99%
“…The phenomenon of localised surface plasmon resonance (LSPR), giving rise to characteristic optical extinction and strong local electromagnetic field enhancement [165], is currently of significant practical interest for applications in sensing, detection and imaging, as well as for optical components and collar cell technologies stimulating the development of novel and sophisticated NP-based systems [166][167][168][169][170]. Controllable assembling of NPs into films or composites allows for conductivity tuning from the variable range hopping to metal-like charge transfer mechanisms opening a way for the fabrication of unique electronic and electro-mechanical devices [171][172][173][174][175]. The NP-filled materials are also of high interest for microwave technologies, bactericidal coatings and membranes, as well as for the formation of surfaces with controlled morphology, wettability and adhesion [176][177][178][179].…”
Section: Functional Nanoparticle-based Materialsmentioning
confidence: 99%
“…It was found that the percolation threshold ensuring the formation of conductive passes through the assembly can be shifted to very low surface coverages of NPs [215]. Controlling the coverage allows tuning the resistance of the assembled metal nanostructures [174]. This capability was used for the fabrication of passive electronic components (resistors and capacitors) by patterned cluster deposition on paper [61].…”
Section: Nps For Enhanced Sensing and Detectionmentioning
confidence: 99%
“…Network formation is not expected in inorganic materials because of the strength of the primary interactions and the depth of the equilibrium states (i.e., the existence of large energy barriers to reach the next available metastable state). Nevertheless, by significantly increasing the role of surface states, inorganic and metal oxide particles can also organize in networks with different geometries and connectivities. However, controlling the relevant interactions here is challenging and these networks show a large degree of disorder.…”
Section: Introductionmentioning
confidence: 99%